Growth, Survival Rate and Feed Conversion Ratio of Juveniles of Macrobrachium rosenbergii (de Man) Fed with Farm made and Commercial Feeds - B., Madhusoodana Kurup; B., Hari (Fishery Technology, 2025)
Feeding trial was conducted in M. rosenbergii to compare efficiency of the farm made feed (diet FMF) with commercial feeds like CP feed (diet A), Higashi feed (diet B), and Rosen feed (diet C). Dried clam meat was used as the control feed (diet D). Water stability of FMF is found well comparable with the above feeds. Higher specific growth rate was recorded in diet FMF (2.02) that did not vary significantly (p>0.05) among the dietary treatments except in diet D (1.15). Higher survival was recorded in diet FMF (91.07%) followed by diet A (90.48%), diet B (89.68%) and diet C (82.14%) while the survival of the juvenile of M. rosenbergii fed with control diet (37.5%) was significantly (p<0.05) lower compared to other treatments. Feed conversion ratio recorded for diet FMF was comparable with that of diets A and B. Protein efficiency ratio was significantly higher (p<0.05) in diet B (0.86), A (0.78) and FMF (0.77) when compared to diet D (0.31). Cost of diet A and B (200%), C (185%) and control diet (169%) was significantly higher than diet FMF. Results of the present study revealed that the growth, survival and feed conversion ratio of M. rosenbergii fed with farm made feed prepared from the locally available feed ingredients were comparable with those of commercial scampi feeds. As the farm made feed preparation was found very cost effective it can be recommended to the scampi farmers of Kerala to make farming more economically viable and feasible.